Evaluasi Kualitas Pelayanan Menggunakan SERVQUAL dan FUZZY AHP Untuk Meningkatkan Kepuasan Penumpang di Bandara Djalaludin Gorontalo - Lahay, Idham Halid; Wolok, Eduart; Yantu, Irwan (Jurnal Teknik, 2024)
Indonesia, as an archipelagic nation, requires an efficient transportation system to support economic mobility and tourism. Djalaludin Airport in Gorontalo plays a pivotal role in facilitating economic and tourism activities within Gorontalo Province. Airport management, involving operators and service users, aims to deliver high-quality services. However, some service aspects still fall short, particularly in physical facility comfort and process efficiency. This study seeks to identify service attributes that need improvement to enhance overall service quality. A quantitative approach was employed, utilizing SERVQUAL analysis based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data were collected through questionnaires and analyzed using a gap method to measure discrepancies between passenger expectations and perceptions. Attribute prioritization was conducted using Fuzzy AHP to identify key areas for improvement, followed by a fishbone analysis to uncover root causes of the identified issues. The results indicate a service conformity level of 87.61%, but notable negative gaps remain in key attributes, such as air circulation comfort in waiting areas and baggage claim efficiency. Recommendations include increasing air conditioning capacity and optimizing conveyor systems to expedite baggage handling. Improving these core attributes suggests that enhancing service quality at Djalaludin Airport will boost passenger satisfaction and loyalty while supporting sustainable growth in air transportation and tourism sectors in Gorontalo Province.